Outcomes of interferon α and ribavirin treatment for chronic hepatitis C in patients with normal serum aminotransaminases. Issue 11 (21st October 2003) - Hui, C-K; Monto, A; Belaye, T; Lau, E; Wright, T L
Abstract : Introduction: Information on treatment outcomes with interferon plus ribavirin combination therapy in chronic hepatitis C patients with normal alanine aminotransaminase (ALT) levels is limited. Aim: The aims of this study were to assess outcomes of treatment with interferon plus ribavirin in patients with normal ALT levels (normal ALT group, n=52) compared with those with elevated ALT levels (raised ALT group, n=53), and to document the rate at which patients with normal ALT levels have an apparent worsening of disease, as shown by increases in ALT levels. Results: At the end of treatment (week 48), 31 patients (59.6%) in the normal ALT group and 30 patients (56.6%) in the raised ALT group had undetectable hepatitis C virus (HCV) RNA (p=0.75). A sustained virological response (SVR) was achieved in 20 patients (38.5%) in the normal ALT group and in 21 patients (39.6%) in the raised ALT group (p=0.90). Patients were subsequently followed up for a median of 29.8 (interquartile range 25th–75th percentile (IQR) 20.8–36.2) months in the normal ALT group and for a median of 26.1 (IQR 17.7–36.3) months in the raised group (p=0.20) after week 72 of treatment. Among patients without SVR in the normal ALT group, only three patients (9.4%) developed persistently raised ALT levels following therapy. Conclusions: Combination therapy with interferon plus ribavirin is associated with a similar SVR in patients with normal ALT levels compared with those with elevated ALT levels. In patients with normal ALT levels, virological non-response to therapy results in new elevations in serum ALT levels in a small minority only.